History and belonging : representations of the past in contemporary European politics - Berger, Stefan; Tekin, Caner (Making sense of history ;, 2018)
In cultural and intellectual terms, one of the EU's most important objectives in pursuing unification has been to develop a common historical narrative of Europe. Across ten compelling case studies, this volume examines the premises underlying such a project to ask: Could such an uncontested history of Europe ever exist? Combining studies of national politics, supranational institutions, and the fraught EU-Mideast periphery with a particular focus on the twentieth century, the contributors to History and Belonging offer a fascinating survey of the attempt to forge a post-national identity politics.